Rainfall Analysis in Kebun Rambutan oil palm plantation PT Perkebunan Nusantara III with water balance model - Aldilla Pratiwi Tanjung; Sumono Sumono; Lukman Adlin Harahap (Universitas Sumatera Utara, 2013)
Oil palm has been rumored as a plant which more water consumption, therefore a research is needed with water balance model to arrange and analyze rainfall parameters as a water source at Kebun Rambutan PT Perkebunan Nusantara III during March-July 2013. Water balance model consist of rainfall, throughfall, stemflow, interception, actual evaporation and runoff. The results showed that the soil at the site has Ultisol land order with sandy clay loam texture and bulk density of, 1,284 g/cm3, particle density of 2,663 g/cm3, porosity of 51,471% and soil organic matter of 2,275%. Daiy rainfall during the research was 3,456 mm/day, however based on yhe calculation of 10 years data from BMKG, daily rainfall during March-July was 4,269 mm/day. Actual evaporation was 2,929 mm/day and in field capacity was 358,05 mm, so that 143,837 mm more water as percolation. Keywords : rainfall, oil palm, water balance